Motivation of Officers towards the Results of Vessel Sanitation Hygiene Inspections at Class I Quarantine Center (BKK) Banten - Budiman; Lukman Waris; Ismarina (Health and Technology Journal (HTechJ), 2024)
The spread of infectious diseases through sea transportation has become a global threat to public health. In this context, the role of the Banten Class I Health Quarantine Center (BKK) is crucial to ensure that ships entering the port area meet cleanliness and sanitation standards. This study explores the motivation of Class I Banten Health Quarantine Center (BKK) officers and the performance of Ship Sanitation Hygiene (HSK) inspection results in the Banten port area. The method used is qualitative. With 12 participants working in BKK Class I. In qualitative research using the "Rapid Assessment Procedure" (RAP) research design, motivational variables such as hope, orientation, enthusiasm, optimism, and valence were explored in their relationship to the quality of HSK examination results. These findings provide important insights for the management of BKK Class I Banten to increase the motivation and performance of officers in carrying out HSK inspection duties. Recommendations from this study can help improve the effectiveness of managing ship cleanliness and sanitation at the port of Banten and reduce the risk of spreading disease through sea transportation.